1998
DOI: 10.2337/diabetes.47.4.523
|View full text |Cite
|
Sign up to set email alerts
|

Basal hepatic glucose production is regulated by the portal vein insulin concentration.

Abstract: The ability of portal vein insulin to control hepatic glucose production (HGP) is debated. The aim of the present study was to determine, therefore, if the liver can respond to a selective decrease in portal vein insulin. Isotopic ([3H]glucose) and arteriovenous difference methods were used to measure HGP in conscious overnight fasted dogs. A pancreatic clamp (somatostatin plus basal portal insulin and glucagon) was used to control the endocrine pancreas. A 40-min control period was followed by a 180-min test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
2
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 11 publications
3
97
2
1
Order By: Relevance
“…This could in part reflect the insulin-resistant state of the subjects but it is also possible that the lipolytic rate was low in these animals due to a neurosuppressive effect of the sedative used, thus further insulin-mediated suppression of lipolysis would be difficult to detect. Nevertheless, since the animals were in the fasted state, this finding does indicate that the insulin-mediated glucose lowering observed after treatment with either agent represents a direct effect of insulin to suppress hepatic glucose production and/or to increase peripheral glucose uptake [20] rather than an indirect effect mediated by lowering NEFA [21].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This could in part reflect the insulin-resistant state of the subjects but it is also possible that the lipolytic rate was low in these animals due to a neurosuppressive effect of the sedative used, thus further insulin-mediated suppression of lipolysis would be difficult to detect. Nevertheless, since the animals were in the fasted state, this finding does indicate that the insulin-mediated glucose lowering observed after treatment with either agent represents a direct effect of insulin to suppress hepatic glucose production and/or to increase peripheral glucose uptake [20] rather than an indirect effect mediated by lowering NEFA [21].…”
Section: Discussionmentioning
confidence: 89%
“…Available evidence, however, suggests that it is likely due to a direct effect of insulin to switch the liver from a state of production to one of uptake and storage [20]. Such a direct effect is also supported by the observation that NEFA (potential mediator of insulin-induced reduction of hepatic glucose output) were suppressed similarly in the control and nateglinide-treated and repaglinide-treated groups.…”
Section: Discussionmentioning
confidence: 93%
“…HOMA-IR index was greater in subjects with IFG than in subjects with NGT or IGT. Since HGP is the primary determinant of the fasting plasma glucose concentration [19] and the FPI concentration is the primary regulator of HGP [20], the product of FPG and FPI primarily reflects hepatic insulin resistance. Whole body insulin sensitivity measured with WBISI index was also reduced in subjects with isolated IFG compared to those with NGT.…”
Section: Discussionmentioning
confidence: 99%
“…The HOMA-IR index was calculated as the product of fasting plasma insulin (FPI) and FPG divided by 22.5 [18]. Since hepatic glucose production (HGP) is the main determinant of FPG concentration [19], and FPI concentration is the main regulator of HGP [20], HOMA-IR index is practically a measure of hepatic insulin resistance. In addition, in order to have an estimate of muscle insulin resistance, we used whole body insulin sensitivity index (WBISI), which was developed by Matsuda & DeFronzo and integrates plasma glucose and insulin concentrations during the OGTT [21].…”
Section: Methodsmentioning
confidence: 99%
“…A large body of evidence concerning hepatic glucose metabolism during exercise in diabetes has been derived from animal experiments [18][19][20][21][22] but there is a lack of in vivo human data. Human studies using magnetic resonance spectroscopy (MRS) have reported defects in mobilisation of hepatic glycogen stores in patients with type 1 diabetes [23,24].…”
Section: Introductionmentioning
confidence: 99%